Microglial clock dysfunction during neuroinflammation impairs oligodendrocyte progenitor cell recruitment and disrupts neuroimmune homeostasis - Lu, Qingqing; Kim, Jin Young (Frontiers in Immunology, 2025)
IntroductionCircadian clocks generate daily physiological rhythms and regulate immune functions, including cytokine production and inflammatory responses. Although time-of-day–dependent variation in microglial immune activity has been reported, how intrinsic microglial clocks respond to neuroinflammatory stimuli and influence microglial function remains unclear.MethodsWe induced neuroinflammation via intraperitoneal injection of lipopolysaccharide (LPS) and isolated microglia from control and LPS-treated mouse brains. To examine circadian clock dynamics and downstream targets, we performed time-series gene expression analyses. To assess the functional relevance of microglial clocks, we transplanted either wild-type or Bmal1-deleted microglia, as well as control or neuroinflammatory microglia, into the corpus callosum of NG2DsRed reporter mice and evaluated oligodendrocyte progenitor cell (OPC) recruitment.ResultsLPS-induced neuroinflammation triggered a phase shift in the core clock gene Bmal1 and disrupted the rhythmic expression of its targets, including Per1, Iba1, Itgam, and Ccl5, resulting in sustained microglial activation. Transplanted wild-type microglia effectively recruited OPCs, whereas both Bmal1-deleted and neuroinflammatory microglia failed to recruit OPCs, indicating that disrupted microglial clock function promotes persistent activation and impairs glial–glial communication.DiscussionThese findings identify microglial circadian clocks as key regulators of homeostatic function and glial–glial communication. Preserving intrinsic clock function in microglia may represent a strategy to mitigate neuroinflammatory damage and support white matter integrity.